2004
DOI: 10.1108/19852510480000658
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions Towards Accounting Career Among Malaysian Undergraduates

Abstract: In the late 20th Century and the early part of the 21st Century, the accounting profession has suffered some setback in its image. The recent scandal involving Enron and Arthur Andersen may have an adverse impact on the career choice of accounting students. On the other hand Malaysia needs more accountants to assist the country to achieve developed nation status by year 2020. Therefore, this study is an attempt to determine whether accounting students still prefer to become accountants and to compare the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…In Malaysia, several studies have shown that the accounting profession is still popular amongst university students (Samidi and Tew 1995;Said, Ghani, Hashim and Mohd Nasir, 2004). A study by Samidi and Tew (1995) reported that majority future accounting graduates had chosen accounting as a profession.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Malaysia, several studies have shown that the accounting profession is still popular amongst university students (Samidi and Tew 1995;Said, Ghani, Hashim and Mohd Nasir, 2004). A study by Samidi and Tew (1995) reported that majority future accounting graduates had chosen accounting as a profession.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Samidi and Tew (1995) reported that majority future accounting graduates had chosen accounting as a profession. Said et al (2004) and Ghani, Said, Mohd Nasir and Jusoff (2008) found that the accounting profession is ranked amongst the most preferred careers by the public and private university students. Unfortunately, despite their interest in the profession, not many especially the Bumiputra graduates have continued on to pursue professional qualifications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The accounting profession has undergone some setback in its image in the late 20 th century and the early part of the 21 st century (Said, Ghani, Hashim, & Mohd Nasir, 2004). Corporate scandal in accounting field is said to be a serious issue these days.…”
Section: Problem Statementmentioning
confidence: 99%
“…Albeit the increase in popularity of accounting courses in Malaysia (Said et al, 2004), the number of students who will prefer to become accountants after completing their studies is still unknown.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation